Knee Septic Arthritis after Arthroscopy: Incidence, Risk Factors, Functional Outcome, and Infection Eradication Rate - Balato, G.; Di Donato, S. L.; Ascione, T.; D'Addona, A.; Smeraglia, F.; Di Vico, G.; Rosa, D. (Joints, 2017)
Purpose Septic knee arthritis following arthroscopy is a rare but dreaded complication. Definition and management of knee deep infections are quite discussed in literature. In this review, literature regarding infections after knee arthroscopy is analyzed highlighting the incidence, causative bacteria, risk factors as well as clinical outcomes.Methods We performed a review of the literature matching the following key words: “septic arthritis” OR “infection” AND “arthroscopy” AND “knee.” Knee arthroscopic procedures, such as debridement, meniscectomy, meniscus repair, synovectomy, microfracture, and lateral release, were considered. Complex procedures, such as ligament reconstruction, fractures, or complex cartilage repair techniques, were not included.Results Thirteen studies were included in this review. Incidence of infection ranged from 0.009 to 1.1% in patients undergoing simple arthroscopic procedures. Staphylococci are the most commonly isolated organisms from postarthroscopy infection. Use of intraoperative intra-articular steroids, smoking, obesity, male sex, diabetes, number of procedures performed during surgery, time of surgery, and tourniquet time of more than 60 minutes have been certified as risk factors for knee infection.Conclusion Postarthroscopy septic arthritis of the knee causes significant morbidity, usually requiring readmission to the hospital, at least one additional operation, and prolonged antibiotic therapy, both intravenous and oral. Prompt diagnosis and treatment are associated with a high success rate.Level of Evidence Level IV, systematic review of I-IV studies.
Keywords: infection; septic arthritis; knee; arthroscopy; risk factors